2010
DOI: 10.2298/aoo1002008s
|View full text |Cite
|
Sign up to set email alerts
|

The role of higher thoracic irradiation doses in patients with limited stage of small-cell lung cancer: Retrospective study

Abstract: Background: Small-cell lung cancer is highly chemo- and radiosensitive tumor. We evaluated two different radiotherapy doses applied sequentially with chemotherapy in relation to time to progression, progression free survival, and overall survival in patients with limited disease of small cell lung cancer. Methods: From 1998 to 2003, 81 patients were treated for small-cell lung carcinoma. Median age was 57 years (range, 36-77 years) and female: male ratio was 1:4. Patients were initially treated with four cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A further 16 and 2 studies reported on PCI and maintenance therapies following induction chemotherapy in first-line SCLC, respectively. Twenty-six studies reported disease functioning scales, most commonly the ECOG performance status (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or the Karnofsky performance status (31)(32)(33)(34)(35)(36). Demographics of patients from the quantitative studies matched the SCLC patient profile described in the literature (37), whereby patients are likely to be male and over 50 years of age.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 16 and 2 studies reported on PCI and maintenance therapies following induction chemotherapy in first-line SCLC, respectively. Twenty-six studies reported disease functioning scales, most commonly the ECOG performance status (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or the Karnofsky performance status (31)(32)(33)(34)(35)(36). Demographics of patients from the quantitative studies matched the SCLC patient profile described in the literature (37), whereby patients are likely to be male and over 50 years of age.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The remaining patients in these studies received either PCDE (cisplatin, cyclophosphamide, doxorubicin, etoposide), PEI (cisplatin, etoposide, ifosfamide), CAV (cyclophosphamide, doxorubicin, vincristine), cyclophosphamide or amrubicin regimens. A slight preference of cisplatin was found over carboplatin in studies which included patients who had received a platinum-based regimen (15,(41)(42)(43)(44)(45)(46)(47). Surgical resection followed by chemotherapy or chemoradiotherapy was used in 4 studies, in which all patients had either stage I or stage II disease under the TNM classification system.…”
Section: Limited Stagementioning
confidence: 99%